Cities and Specialisation: Evidence from South Asia. - Fafchamps, M; Shilpi, F (2005)
Using survey data from Nepal, we examine the relationship between proximity to urban centres and the organisation of labour. We show that wards located in and near cities have more diversified and more market oriented activities. This suggests the presence of returns to market specialisation in cities. We also find some evidence of returns to hierarchical specialisation. These effects are felt up to four hours of travel time from large cities. Urbanisation is associated with lower female labour market participation and with a more pronounced specialisation of women either in market-related activities or in strictly home-based chores.